An Analysis Of Village Official's Perception Of The Village Financial System (Siskeudes) - Pratiwi, Desy Nur (Jurnal ASET (Akuntansi Riset), 2020)
The articel aims to influence the use of Siskeudes application with the Technology Acceptance Model (TAM) approach conducted in Sukoharjo Regency. This research uses primary data in the form of a questionnaire given to village officials in the financial management section. The technique of sample collection with convenience sampling method and produced a sample of 34 villages. Hypothesis testing uses path analysis with multiple linear regression. Results of partial test shows perceived ease of use and perceived usefulness affect the interest in using technology, perceived usefulness and the interest in using technology directly influence the use of Siskeudes, while perceived ease of use has no effect on the use of Siskeudes, it is also found indirectly perceived usefulness through behavioral intention to use has no effect on the use of Siskeudes and indirectly perceived usefulness through behavioral intention to use does not have an effect on the use of Siskeudes. Â The implications of this research provide information about all village officials that are easily understood by the siskeudes in the preparation of village fund reportsKeywords: behavioral intention, perceived usefulness, perceived ease of use, and Siskeudes